Occurrence, development and natural enemies of cecidogenous generations of Pemphigus gairi Stroyan (Sternorrhyncha, Pemphigidae) - J. Urban (Journal of Forest Science, 2004)
The paper deals with the occurrence, development and natural enemies of the cecidogenous aphid Pemphigus gairi Stroyan (Pemphigidae). The aphid abundantly occurred on leaves of Populus nigra and P. nigra var. italica in Brno in 2003. It was described from England and no information on its occurrence is available in literature from continental Europe. It refers to a holocyclic and heteroecious species. In localities under study, larvae of fundatrices hatched mainly in the last decade of April. Through their sucking on the abaxial face of freshly unfolded leaves of poplars, species-unspecific lengthwise tile-like galls originate on the adaxial face of leaves (near the central leaf vein). During 12 to 14 days, fundatrices mature in galls of an average length and width 11.2 and 3.9 mm, respectively. Adults live about 1.5 months, namely max. until mid-July. They produce on average 75.6 fundatrigeniae which mature to winged migrantes alatae in the course of 16 days. In the period of hatching the first migrants (at the end of May), galls grow up to the final length of about 11.8 mm and width 4.7 mm. In primary slit-shaped caps on the abaxial face of leaves, migrants leave the galls through emergence holes. In a secondary host (Aethusa cynapium, Daucaceae), they produce on average about 17.5 larvae of exules. Owing to natural enemies (above all true bugs of the species Anthocoris minki), aphids die in 90% of galls.